2019
DOI: 10.1002/gps.5225
|View full text |Cite
|
Sign up to set email alerts
|

The geography of suicide in older adults in Hong Kong: An ecological study

Abstract: Objectives:The geography of suicide has been widely explored among the general population. However, little is known of the geographic variations in suicides among the older adults and their spatial correlates. This study aims to explore the spatial variations in the elderly suicide rates and their correlates in Hong Kong.Methods: Bayesian hierarchical models have been used to estimate smoothed standardized mortality ratios (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) on suicide in people aged 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…So far, regional factors affecting suicide have been found to be related to the average income level of residents in the area [9,11,12], the average educational level, the employment or unemployment rate [9], socioeconimic characteristics of the region such as the financial independence of the region [7], the percentage of single-person households in the area [10], the population density [7,10], the divorce rate [7], the health and welfare budget [7], and social infrastructure such as medical institutions and leisure facilities [7]. In other words, the suicide rate was reported to be higher in economically disadvantaged regions [9,11,12] and in regions with a higher divorce rate [10]. In addition, areas with a low population density and with a high percentage single-person households were reported to have a higher rate of suicide related to loneliness [10], and the self-harm rate was higher in areas with a higher unemployment rate and a higher average age [9].…”
Section: Introduction 1 Backgroundmentioning
confidence: 99%
“…So far, regional factors affecting suicide have been found to be related to the average income level of residents in the area [9,11,12], the average educational level, the employment or unemployment rate [9], socioeconimic characteristics of the region such as the financial independence of the region [7], the percentage of single-person households in the area [10], the population density [7,10], the divorce rate [7], the health and welfare budget [7], and social infrastructure such as medical institutions and leisure facilities [7]. In other words, the suicide rate was reported to be higher in economically disadvantaged regions [9,11,12] and in regions with a higher divorce rate [10]. In addition, areas with a low population density and with a high percentage single-person households were reported to have a higher rate of suicide related to loneliness [10], and the self-harm rate was higher in areas with a higher unemployment rate and a higher average age [9].…”
Section: Introduction 1 Backgroundmentioning
confidence: 99%
“…15 An ecological study in Hong Kong indicated that neighborhood speci c features, such as recreational services, daily necessity resources, and community centers, were signi cantly associated with suicides in older adults. 39 In this study, higher levels of rurality assessed by population density were associated with an increased risk of suicide in males but not necessarily in females. Especially among males aged 0-39 years, population density was the strongest variables associated with an increased risk of suicide.…”
Section: Socioeconomic Correlates Of Gender-age-speci C Suicidesmentioning
confidence: 53%
“… 16 An ecological study in Hong Kong indicated that neighbourhood-specific features, such as recreational services, daily necessity resources and community centres, were significantly associated with suicide rates in older adults. 42 …”
Section: Discussionmentioning
confidence: 99%